2010
DOI: 10.1007/s00431-009-1126-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful cord blood transplantation for a CHARGE syndrome with CHD7 mutation showing DiGeorge sequence including hypoparathyroidism

Abstract: It is rare that coloboma, heart anomalies, choanal atresia, retarded growth and development, and genital and ear anomalies (CHARGE) syndrome patients have DiGeorge sequence showing severe immunodeficiency due to the defect of the thymus. Although the only treatment to achieve immunological recovery for these patients in countries where thymic transplantation is not ethically approved would be hematopoietic cell transplantation, long-term survival has not been obtained in most patients. On the other hand, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…For 23 of 26 (88%) patients, T-cell lymphopenia was concomitant with T-cell dysfunction. 14,17,18,20,[22][23][24][25][26][27][28][29][30][31]33,[35][36][37] In our collected cohort, B-and/or NK-cell numbers were reported in only 29 of 59 patients, and of these 29 patients, 1 had low B-cell numbers, 1 had high B-cell numbers, 1 had low NK-cells numbers and 3 had high NK-cell numbers. The reported B-and NK-cells numbers of other patients were normal.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 77%
See 1 more Smart Citation
“…For 23 of 26 (88%) patients, T-cell lymphopenia was concomitant with T-cell dysfunction. 14,17,18,20,[22][23][24][25][26][27][28][29][30][31]33,[35][36][37] In our collected cohort, B-and/or NK-cell numbers were reported in only 29 of 59 patients, and of these 29 patients, 1 had low B-cell numbers, 1 had high B-cell numbers, 1 had low NK-cells numbers and 3 had high NK-cell numbers. The reported B-and NK-cells numbers of other patients were normal.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 77%
“…T-cell lymphopenia in our collected cohort was associated with thymic aplasia or hypoplasia in 21 of 22 (95%) patients. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] T-cell function by response on mitogens was available for 28 of 59 patients and of these 28 patients 24 (86%) had a low or absent response on mitogen. For 23 of 26 (88%) patients, T-cell lymphopenia was concomitant with T-cell dysfunction.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
“…In particular, thymus aplasia and hypoparathyroidism are increasingly recognised in CHARGE syndrome and mark the clinical overlap with the DiGeorge phenotype of 22q11 deletions 50 51. In approximately 85% of VCFS patients, a common 3 Mb heterozygous deletion of 22q11.2 is present, resulting in TBX1 haploinsufficiency.…”
Section: Phenotypic Spectrum Of Patients With a Mutation In The Chd7 mentioning
confidence: 99%
“…[131][132][133][134][135][136][137] For complete DiGeorge anomaly, a review of 17 treated patients demonstrated 41% overall survival. 136 Although patients develop normal T cell numbers through clonal expansion and normal proliferative responses to PHA, a significant issue that remains unaddressed involves persistent lack of thymic function.…”
Section: Bone Marrow Transplant or Mature T-cell Infusionsmentioning
confidence: 98%